Fixação das fraturas do platô tibial com placas pela via de acesso posterior - relato preliminar de 12 casos - Wajnsztejn, André [UNIFESP] (2011)
OBJECTIVE: To describe our preliminary results of posterior shearing tibia plateau fractures treated by a direct dorsal approach and plate fixation. METHODS: A consecutive series of twelve patients with tibia plateau fractures treated by direct posterior approach was selected from our database. Conventional radiographies, computed tomography scans and medical records were reviewed. All cases were followed to union, as defined by painless weight bearing and radiographic healing. RESULTS: Between July 2009 and April 2010, our trauma service received 89 tibia plateau fractures and treated 80 (89,9%) operatively. Twelve patients (13,5%) sustained posterior shearing tibia plateau fractures. All fractures were treated through the posterior approach, although 3 required association with an anterolateral approach as well. The mean age of patients was 35 years and mean follow-up was 12 (range 8-23) months. The fractures were classified according to AO/OTA: five 41 B1, four 41 B3, two 41 C1 and one 41 C3. There was one wound dehiscence, managed with local wound care, and one loss of reduction treated by reoperation. No patient sustained neurovascular injury, nonunion, malunions or knee instability. In four cases the reduction was rated as poor (> 2 mm step off), in five cases reduction was rated as imperfect (<2 mm step off) and in three cases the reduction was rated as anatomic (absolutely no step-off). CONCLUSION: Authors conclude that posterior approaches should be considered when tibial plateau fractures result in posterior displaced fragments. A larger sample is needed to get definitive conclusions.